Development of Job Rotation Model for Performance Improvement of Employees of East Java I Regional Office of Directorate General of Customs and Excise - Harwan Ony Prasetyanto (Airlangga Development Journal, 2020)
Job rotaion in public service agencies is a common practice. Job rotations are implemented in order for employees to gain new experience, learn new things that can ultimately improve the skills, competencies and performance that are beneficial for the organization. The Directorate General of Customs and Excise (DJBC) of Republic of Indonesia applies the homebase (within the city of residence) and non-homebase (far from the city of residence) job rotation models in an effort to improve employee experience, skills, competencies and performance and meet the organization’s specific goals. This study aimed to identify the degree of engagement and performance of DJBC East Java I Regional Office employees who have experienced both homebase and non-homebase job rotation models. The study used qualitative methods with a number of informants selected purposively based on their age range and homebase and non-homebase job rotation experience. The results showed that non-homebase job rotation that was originally intended to provide employees with experience, knowledge, skills and improvement is not accompanied with strong employee engagement nor a high degree of work performance. Personal and family problems, unexpected financial expenditure and the process of adaptation in the new workplace have prevented the non-homebase employees from developing optimum engagement and job performance